2016
DOI: 10.1155/2016/5830835
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Preloaded DMEK Lenticules in Dextran and Non-Dextran-Based Organ Culture Medium

Abstract: Purpose. To determine the optimum preservation conditions for preloading DMEK lenticules using organ culture system. Methods. 8.5 mm DMEK lenticules were stripped and preserved with endothelium flap-in for 4 days at RT in an IOL cartridge that was blocked with rubber stoppers from each end. In C1, tissues were collected from tissue culture medium (TCM) and preserved in TCM. In C2, tissues were collected from transport medium (TCM + 6% dextran T500) (TM) and preserved in TM. In C3, tissues were collected from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Our previous study has shown that excising a DMEK graft that has been stored in dextran-based medium is easier (100% success) compared with excision from organ culture media without dextran (76% success). 18 Standardised preparation methods may further reduce graft wastage. In our earlier studies we have shown that preloading a DMEK graft in an IOL cartridge does not lead to significant cell loss (<10%) when preserved in dextran-based medium at RT for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that excising a DMEK graft that has been stored in dextran-based medium is easier (100% success) compared with excision from organ culture media without dextran (76% success). 18 Standardised preparation methods may further reduce graft wastage. In our earlier studies we have shown that preloading a DMEK graft in an IOL cartridge does not lead to significant cell loss (<10%) when preserved in dextran-based medium at RT for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…[19] On the other hand, Yoeruek and Bayyoud reported only a moderate loss of endothelial cells in precut tissue and safe donor graft preparation with or without dextran. [20,21] Parekh et al [22] concluded that dextran should be used in precut tissues to prevent the loss of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…One separate positive sample was induced with apoptosis using TACS nuclease and all the samples were viewed and imaged using inverted light microscope (Nikon Eclipse TS100, Nikon, Surrey, UK). The apoptotic cells were manually counted, and an average was recorded from five random areas (36).…”
Section: Cell Apoptosis Using Terminal Deoxynucleotidyl Transferase D...mentioning
confidence: 99%